2013
DOI: 10.1016/j.bbabio.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concepts in the flavinylation of succinate dehydrogenase

Abstract: The Succinate Dehydrogenase (SDH) heterotetrameric complex catalyzes the oxidation of succinate to fumarate in the tricarboxylic acid (TCA) cycle and in the aerobic respiratory chains of eukaryotes and bacteria. Essential in this catalysis, is the covalently-linked cofactor flavin adenine dinucleotide (FAD) in subunit1 (Sdh1) of the SDH enzyme complex. The mechanism of FAD insertion and covalent attachment to Sdh1 is unknown. Our working concept of this flavinylation process has relied mostly on foundational w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 67 publications
(149 reference statements)
1
49
0
1
Order By: Relevance
“…17 From these combined results, it has been proposed that SdhE/5 interacts with SdhA/1 to mediate flavinylation, yet the molecular details of this process remain unresolved. 15,18 To examine the molecular mechanism of SdhE-dependent flavinylation of SdhA, this study describes truncation and sitedirected mutagenesis of residues conserved across bacterial homologues of SdhE. Using phenotype rescue assays, we demonstrated that a highly conserved RGxxE motif is required for flavinylation and activation of SDH activity.…”
mentioning
confidence: 98%
“…17 From these combined results, it has been proposed that SdhE/5 interacts with SdhA/1 to mediate flavinylation, yet the molecular details of this process remain unresolved. 15,18 To examine the molecular mechanism of SdhE-dependent flavinylation of SdhA, this study describes truncation and sitedirected mutagenesis of residues conserved across bacterial homologues of SdhE. Using phenotype rescue assays, we demonstrated that a highly conserved RGxxE motif is required for flavinylation and activation of SDH activity.…”
mentioning
confidence: 98%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 16 [17], (c) [68], (d) [69], (e) [70], (f) [71], (g) [72], (h) [73], (i) [74], (j) [75], (k) [76], (l) [77], (m) [22], (n) [29], (o) [78], (p) [58], (q) [79], (r)[34] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 ((a) [48], (b) [45], (c) [47], (d) [43], (e) [44], (f) [39], (g) …”
Section: Resultsunclassified
“…NADH is localized mainly in the mitochondria and participates predominantly in cellular energy metabolism, while FAD is contained in both cytoplasm and mitochondria and is involved, apart from oxidative phosphorylation, in various biochemical processes (glutathione utilization, lipogenesis, lipid peroxidation, antioxidant reactions, acetyl coenzyme A synthesis, the glutathione-ascorbate cycle, the pentose phosphate cycle), which considerably complicates data analysis [4,13,21,27].…”
Section: Cofactors Nadn and Fad And Their Role In Cellular Energy Metmentioning
confidence: 99%